Analisis Kinerja Sistem Informasi Akademik Menggunakan Metode TRADE Pada Universitas Tridinanti Palembang - Ahmad Faizal; Rusmala Santi; Catur Eri Gunawan (APTIKOM SUMSEL, 2020)
Palembang Tridinanti University has an academic information system created with the aim to facilitate lecturers, students and employees in the lecturing process of Tridinanti University in Palembang. then it needs to be reviewed to analyze the performance of academic information systems at Tridinanti University, Palembang. Therefore it is necessary to hold performance measurements to find out whether the academic information system is in accordance with what is expected. The measurement methods used are observation, interviews, questionnaires, and documentation. Then performance measurements are carried out to determine the performance of the running system using the method of performance measurement according to Training Resources Data Exchange (TRADE). The results of this study are used as recommendations for improvement so that the performance of the academic information system at Palembang's Tridinanti University can run according to the target